If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6 = 30 + x Reorder the terms: 6 + 5x = 30 + x Solving 6 + 5x = 30 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6 + 5x + -1x = 30 + x + -1x Combine like terms: 5x + -1x = 4x 6 + 4x = 30 + x + -1x Combine like terms: x + -1x = 0 6 + 4x = 30 + 0 6 + 4x = 30 Add '-6' to each side of the equation. 6 + -6 + 4x = 30 + -6 Combine like terms: 6 + -6 = 0 0 + 4x = 30 + -6 4x = 30 + -6 Combine like terms: 30 + -6 = 24 4x = 24 Divide each side by '4'. x = 6 Simplifying x = 6
| 30xm+15xn-20ym-10yn= | | 25x^4-81y^2=0 | | 1/4x=x-33 | | 5-(-3)+6= | | f(x)=-4x^2+16x-5 | | x/(36x^2-9) | | x+2x+5x=32 | | x^2+14xy+24y=0 | | 5+4ln(x)=7 | | x/36x^2-9 | | m^2+22m-4=0 | | y^4-6y^3+12y^2-10y+3= | | a=-1e+-1s+-1y | | w^2-13w+42.25=0 | | 1/4x^4-9/25=0 | | ydx=x(lnx-lny)dy | | 5x=(3x-3)(m+4) | | 0.90n=n+15 | | -17+8x=14 | | 0.75p=18 | | 8x-4x+5=x-5+10 | | 2x+40=9x-2 | | 0=1/3x=1 | | 11r+60=15 | | 8(v+3)-2v=3(2v+4)-18 | | 3(x-8)=x+2 | | a=cx+bc | | 11x-12=5(2x+3)-3 | | 6/27 | | 0.06t+0.09(t+500)=150 | | 2x+17=9x-4 | | 2(t-3)-5(5t-6)=9-6(7t-5) |